TRANSFORMATION OF THE ACCOUNTING SYSTEM OF UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESSES - Кругла, Марина (SWorldJournal, 2025)
Ukraine is transforming its accounting system as part of European integration, harmonizing its legislation with EU standards to increase the transparency and quality of financial information. Recent changes include the introduction of mandatory sustainabi